Companion Proceedings of the Web Conference 2020 2020
DOI: 10.1145/3366424.3385775
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Coordinated Groups Behind White Helmets Disinformation

Abstract: Propaganda, disinformation, manipulation, and polarization are the modern illnesses of a society increasingly dependent on social media as a source of news. In this paper, we explore the disinformation campaign, sponsored by Russia and allies, against the Syria Civil Defense (a.k.a. the White Helmets). We unveil coordinated groups using automatic retweets and content duplication to promote narratives and/or accounts. e results also reveal distinct promoting strategies, ranging from the small groups sharing the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 12 publications
2
53
0
Order By: Relevance
“…Similarly, HCCs discovered by the three community extraction methods (Table 7) exhibit large discrepancies, suggesting that whichever method is used, tuning is required to produce interpretable results. This is evident in the literature: Cao et al conducted significant pre-processing when identifying URL sharing campaigns across two years of Twitter activity (Cao et al 2015), and Pacheco et al showed how specific strategies could identify groups in the online narrative surrounding the Syrian White Helmet organisation (Pacheco et al 2020).…”
Section: Hcc Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, HCCs discovered by the three community extraction methods (Table 7) exhibit large discrepancies, suggesting that whichever method is used, tuning is required to produce interpretable results. This is evident in the literature: Cao et al conducted significant pre-processing when identifying URL sharing campaigns across two years of Twitter activity (Cao et al 2015), and Pacheco et al showed how specific strategies could identify groups in the online narrative surrounding the Syrian White Helmet organisation (Pacheco et al 2020).…”
Section: Hcc Detection Methodsmentioning
confidence: 99%
“…The approach presented can be used to perform analytics similar to the Rapid Retweet Network used by Pacheco et al (2020), who used it to expose tight clusters of bot-like accounts, which retweeted the same tweet within 10 s of it appearing. We varied this for the DS1 dataset (due to its small nature) and searched for accounts which retweeted the same tweet within 10 s, regardless of the age of the original tweet.…”
Section: Validation Of Inauthentic Behaviour Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current information ecosystem and virality tools, such as bots, enable memes to spread easily, jumping from one target group to another. As of present, attempts to limit the spread of such memes have focused on analyzing social networks and looking for fake accounts and bots to reduce the spread of such content (Cresci et al, 2017;Yang et al, 2019;Chetan et al, 2019;Pacheco et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Propaganda appears in various forms and has been studied by different research communities. There has been work on exploring network structure, looking for malicious accounts and coordinated inauthentic behavior (Cresci et al, 2017;Yang et al, 2019;Chetan et al, 2019;Pacheco et al, 2020).…”
Section: Introductionmentioning
confidence: 99%